GapA, a potential vaccine candidate antigen against Streptococcus agalactiae in Nile tilapia (Oreochromis niloticus). Issue 63 (April 2017) - Zhang, Ze; Yu, Angen; Lan, Jiangfeng; Zhang, Hua; Hu, Minqiang; Cheng, Jiewei; Zhao, Lijuan; Lin, Li; Wei, Shun
Abstract: Streptococcosis due to the bacterium Streptococcus agalactiae ( S. agalactiae ) has resulted in enormous economic losses in aquaculture worldwide, especially in the tilapia culture industry. Previously, there were limited vaccines that could be employed against streptococcosis in tilapia. This study aimed to develop a vaccine candidate using the glyceraldehyde-phosphate dehydrogenase protein (GapA) of S. agalactiae encoded by the gapA gene. Tilapia were intraperitoneally injected with PBS, PBS + Freund's adjuvant, PBS + Montanide's adjuvant, GapA + Freund's adjuvant, GapA + Montanide's adjuvant, killed S. agalactiae whole cells (WC)+Freund's adjuvant, or killed S. agalactiae whole cells (WC)+ Montanide's adjuvant. They were then challenged with S. agalactiae, and the relative percentage survival (RPS) was monitored 14 days after the challenge. The highest RPSs were observed in the WC groups, with 76.7% in WC + Freund's adjuvant and 74.4% in WC + Montanide's adjuvant groups; these were followed by the GapA groups, with 63.3% in GapA + Freund's adjuvant and 45.6% in GapA + Montanide's adjuvant groups. The RPS of the PBS group was 0%, and those of PBS + Freund's adjuvant and PBS + Montanide's adjuvant groups were 6.7% and 3.3%, respectively. Additionally, the IgM antibody responses elicited in GapA groups and WC groups were significantly higher than those in PBS groups. Furthermore, the expressions of cytokine (IL-1β and TNF-α) mRNAs in the GapA groups and WC groups were significantly higher than those in the PBS groups. Taken together, these results reveal that the GapA protein is a promising vaccine candidate that could be used to prevent streptococcosis in tilapia. Highlights: GapA of Streptococcus agalactiae was expressed and purified in this study. The GapA subunit vaccine can provide protection against Streptococcus agalactiae infection in tilapia. Freund's adjuvant might be better for tilapia vaccines compared with Montanide's adjuvant.